Hardboiled Argentine History: The Dialectical Turns of Self-Deception in Ernesto Mallo's La aguja en el pajar. - Larson, Erik; Adams, Glade (Hispanófila)
This article examines Argentine Ernesto's detective novel La aguja en el pajar (2006). We consider specifically the novel's use of noir narrative tropes to explore Argentine history, particularly the trajectory of the military whose efforts at total dominion ultimately precipitated their own downfall. By so doing, the novel poses the last 50 years of Argentine history as a noir novel in itself, one chock full of dialectical turns and epistemological undercutting. We draw upon Fabio Vighi's theoretical analysis in Critical Theory and Film: Rethinking Ideology through Film Noir (2012) which posits noir narrative as dialectical: the more the antihero schemes, the more he becomes prisoner to his own scheming. Read in this manner, noir narratives have everything to do with self-deception. Mallo's novel similarly explores self-deception as the materia prima of history, as the at-times misguided obsessions that precipitate tragedy, or as utopian dreams for which one is hard-pressed to relinquish, and which sometimes allow one to survive in the midst of state sanctioned violence or bureaucratic corruption, as we see through the heroism of Mallo's hard-boiled detective, Comisario Lascano.